2011
DOI: 10.1016/j.jtcvs.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative left ventricular function and time from infarction on the long-term benefits after intramyocardial CD133+ bone marrow stem cell transplant

Abstract: Intramyocardial stem cell therapy was safe but lacked significant lasting benefits beyond 6 months in our study cohort with a limited number of patients. Preoperative left ventricular ejection fraction and time since myocardial infarction may be critical parameters for selection of patients who can benefit most from intramyocardial stem cell treatment during coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 33 publications
0
30
0
2
Order By: Relevance
“…According to Davy et al [16] enrichment of autologous bone marrow CD34 + stem cells could increase the efficacy of treatments in clinical settings. Despite the fact that CD34 + cells have been the selected option for heart repair, there are also some reports of CD133 + cells applied in clinical trials showing improvement of myocardial viability and local perfusion of the infarcted zone [17][18][19][20][21][22]. However, none of these studies have shown de novo formation of cardiac muscle.…”
Section: Introductionmentioning
confidence: 99%
“…According to Davy et al [16] enrichment of autologous bone marrow CD34 + stem cells could increase the efficacy of treatments in clinical settings. Despite the fact that CD34 + cells have been the selected option for heart repair, there are also some reports of CD133 + cells applied in clinical trials showing improvement of myocardial viability and local perfusion of the infarcted zone [17][18][19][20][21][22]. However, none of these studies have shown de novo formation of cardiac muscle.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Stamm et al described a significant postoperative improvement of the LVEF 6 months after CD133+ cell transplantation in CABG patients with moderately reduced LVEF [10]. However, the same group reported that with regard to the LVEF, combined CABG and cell therapy were not superior to single CABG beyond 6 months after surgery [22]. In fact, they found a LVEF <40% and a time period of 7 to 12 weeks between myocardial infarction and surgery to be predictors of an improvement of the LVEF of at least 5%.…”
Section: Discussionmentioning
confidence: 96%
“…Currently the Multicenter Phase III clinical randomized placebo-control study is carried out [2], following terminated clinical studies Phase I and Phase II [10]. After studies closure all participants of mentioned trials are observed yearly lifelong within the registry program established in our center.…”
Section: Methodsmentioning
confidence: 99%